Assessment of the Effect of Local Application of Exogenous Melatonin on Bone Healing Process - Muhanad Tareq Jehad (Journal of Global Pharma Technology, 2018)
Bone defects have become universal health care difficulty. Bone regeneration involves the differentiation of new cells and the formation of new bone tissues that results in an overall increase in volume of new skeletal tissues. Medical treatments for bone defects have been largely focused on replacing the lost bone with bone grafts materials. Aim of the study: is to evaluate the effect of local application of melatonin on healing of induced bone defect by histological and histomorphometric analysis. Materials and methods: Twenty four adult male rats divided into control and melatonin groups(8 animals) for each healing periods (1,2, and 4 weeks ).Two holes induced in each rat femur ( one hole in right for melatonin application and one in left femur bones). Results: Histological findings indicated that bone defects in the melatonin group showed early bone formation, mineralization and maturation as compared to control ones. Mean values of studied (bone trabecular area and number) were higher in melatonin group and values of (bone marrow area) decreased in 2 and 4 weeks durations. Osteoblasts, osteocytes mean values were higher in melatonin group, osteoclasts highest values shown in 2weeks in control group. Conclusion: The application of melatonin was effective in bone healing process by enhancement of earlier bone formation.Keywords: Bone defect, Melatonin, Histomorphometric analysis.